Preclinical evaluation of pentagamavunone-1 as monotherapy and combination therapy for pancreatic cancer in multiple xenograft models - Naoki Kamitani; Ikuko Nakamae; Noriko Yoneda-Kato; Jun-ya Kato; Masayuki Sho (Scientific Reports, 2022)
Abstract We previously reported that pentagamavunone-1 (PGV-1) effectively inhibited cell proliferation in many types of human tumors, including pancreatic cancer, by inducing M phase (prometaphase) arrest, senescence, and apoptosis with few side effects. However, a detailed evaluation of the effects of PGV-1 on pancreatic cancer cells in an in vivo setting has not yet been conducted. The present study investigated the potential efficacy of PGV-1 as both monotherapy and combination therapy for pancreatic cancer using multiple xenograft mouse assays. A cell-line derived xenograft model (CDX-M) with pancreatic cancer cell line and a patient-derived xenograft mouse model (PDX-M) using resected pancreatic cancer samples without neoadjuvant chemotherapy were established in both heterotopic and orthotopic manners. PGV-1 effectively suppressed tumor formation at the heterotopic and orthotopic sites in CDX-M than in untreated mice. Combination therapy with PGV-1 and gemcitabine more effectively suppressed tumor formation than monotherapy with PGV-1 or gemcitabine when administered after tumor formation. Monotherapy with PGV-1 or gemcitabine less effectively suppressed tumor formation in PDX-M than in CDX-M, whereas combination therapy with PGV-1 and gemcitabine more effectively suppressed tumor formation. PGV-1 as monotherapy and combination therapy with gemcitabine effectively inhibited tumor formation and has potential as an anticancer candidate for pancreatic cancer.